Polynuclear Fe(n) complexes (n = 1, 2, 4, 5) of polytopic hydrazone ligands with Fe(II), Fe(III) and mixed oxidation state combinations - Anwar, Muhammad U; Shuvaev, Konstantin V; Dawe, Louise N; Thompson, Laurence K (Inorganic chemistry, 2011)
The iron coordination chemistry of some polytopic hydrazone based ligands is examined. The complexes derive from a general self-assembly strategy, where ligand design can be used to devise specific polymetallic [n × n] grid architectures. However, as part of any complex equilibrium process, oligomeric entities can also occur, particularly when ligand tautomeric flexibility is considered, and examples of mononuclear, dinuclear, tetranuclear, and pentanuclear complexes have been observed within a related class of ligands. In addition, ligand site donor composition can lead to coordination spheres that stabilize both high spin Fe(II) and Fe(III) sites, with evidence for Fe(II) spin crossover. Structural and magnetic properties are examined, which reveal the presence of antiferromagnetic exchange in the polynuclear systems.